HUBUNGAN MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. BPR DANA NUSANTARA DI KOTA BATAM - Angela Saskia,; Raymond, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The aims of this research is to reveal and analyse  The Relationship between motivation and compensation against  employee’s  performance  at BPR Dana Nusantara. There’re  150 respondent used in this research to be analysed. Details in this  research will be conducted using Multiple Regression Analysis. It’s two  kinds of independence variables on this research, consist of motivation, and compensation and one dependence variable namely employee’s performance..  Three results in this research has been found, and it shown that, motivation influenced positively and significantly to employee’s performance, and the probability of Significance is 0.001 < 0.050, it meant   that 1st hypothesis in this research, accepted. And for the result of 2nd hypothesis shown that compensation influenced positively and significantly to employee’s performance, and the probability of Significance is 0.000 < 0.050, It meant that 2nd hypothesis in this research, accepted.  And for 3rd hypothesis in this research shown that motivation and compensation  simultaneosly influenced positively and significantly to employee’s performance, and the probability of Significance is 0.000 < 0.050, It meant that 3rd hypothesis in this research, accepted. And the amount of adjsuted R square is 73.3% it mean that employee’s performance can be explained by motivation and compensation as much as 73.3% and the rest 26,7%  explained by other variable outside this research.